Analysis and Vision in the History of Modern Economic Thought - Heilbroner, Robert L. (Journal of Economic Literature, 1990)
dominate modern economic history, taking that phrase to refer to the 50-year period from 1939 to 1989. One is the increasing strain on, and eventual structural failure of, centralized planning in virtually all of the self-styled socialist world. The other, less dramatic, but of no less historical significance, is the continued success of capitalism in its major strongholds. In both cases, I use as the crucial but not sole indicator of success or failure the political fortunes of the two social orders. There have been economic successes for socialism-above all, the initial industrialization of the USSR and the early modernization of China; there have been economic failures of capitalisminstability, uneven growth, unsatisfactory income distributions, dangerous international imbalances. From the perspective of the present, however, the half century is remarkable for the political verdict that has finally been passed on the two systems. With few exceptions, socialism has experienced a public delegitimization without precedent in modern, perhaps in all, history; whereas despite its failures, capitalism has enjoyed an uncontestable, and probably rising degree of internal political support. In this paper I shall be concerned only indirectly with these historical developments, for my purpose is neither to describe nor to explain the contrasting fates of the two great social orders. Rather, I wish to review and interpret the manner in which modern developments have been perceived by economists. Thus, as my title indicates, this is an essay in the history of economic thought, not in economic history. But it would be disingenuous not to admit to a more pointed purpose of my investigation. It is to inquire into the successes and failures of economic thought in anticipating the march of actual events. It will come as no surprise that failures have considerably outweighed successes in this endeavor, even excluding the momentous, and utterly unforeseen happenings at the conclusion of the period in 1989. A few observers have offered prognoses of history's long line that were subsequently vindi-